2019
DOI: 10.1111/dme.14084
|View full text |Cite
|
Sign up to set email alerts
|

Addition of low‐dose liraglutide to insulin therapy is useful for glycaemic control during the peri‐operative period: effect of glucagon‐like peptide‐1 receptor agonist therapy on glycaemic control in patients undergoing cardiac surgery (GLOLIA study)

Abstract: Aim To test the hypothesis that the addition of a glucagon‐like peptide‐1 receptor agonist that can decrease glucose levels without increasing the hypoglycaemia risk will achieve appropriate glycaemic control during the peri‐operative period. Methods We studied 70 people with Type 2 diabetes who underwent elective cardiac surgery. Participants were randomized to either an insulin‐alone or an insulin plus liraglutide 0.6 mg/day group. We evaluated average M values, which indicated the proximity index of the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…[94][95][96] Findings from randomised controlled trials suggest preoperative treatment with liraglutide can improve glycaemic control in the perioperative period in patients with and without diabetes (table 2). 88,91,97 In a study of non-ICU patients with type 2 diabetes, treatment with exenatide plus basal insulin resulted in a higher proportion of glucose readings within the target range of 3•9-10•0 mmol/L (78%) compared with exenatide alone (62%) or basalbolus insulin (63%). 68 As expected, trials with GLP-1 receptor agonists have shown increased frequencies of gastrointestinal side-effects.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…[94][95][96] Findings from randomised controlled trials suggest preoperative treatment with liraglutide can improve glycaemic control in the perioperative period in patients with and without diabetes (table 2). 88,91,97 In a study of non-ICU patients with type 2 diabetes, treatment with exenatide plus basal insulin resulted in a higher proportion of glucose readings within the target range of 3•9-10•0 mmol/L (78%) compared with exenatide alone (62%) or basalbolus insulin (63%). 68 As expected, trials with GLP-1 receptor agonists have shown increased frequencies of gastrointestinal side-effects.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…68 As expected, trials with GLP-1 receptor agonists have shown increased frequencies of gastrointestinal side-effects. 68,88,91,97 More research is needed with these drugs to determine if the potential for improved glycaemic control with a reduction of hypoglycaemic events counterbalances the increase in gastrointestinal side-effects in the hospital setting.…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 99%
“…Insulinbedarf und verbesserte glykämische Kontrolle [ 111 ]. Auch die GLOLIA Studie, in der Liraglutid bei Kardiochirurgie als Kombinationstherapie zu Insulin bei Menschen mit DMT2 eingesetzt wurde, ergab perioperativ Hinweise für eine verbesserte Glykämie [ 112 ]. In einem Kollektiv von Menschen mit DMT2 und nicht kardiochirurgischen Eingriffen konnte eine randomisiert-kontrollierte Studie mit Liraglutid (versus Glukose-Insulin-Kalium-Infusion oder i.v.…”
Section: Perioperative Medikamentöse Diabetestherapieunclassified
“…Since the patients would receive STSG surgery recently, insulin pumps were applied for glycaemic control (therapeutic goal: fasting blood glucose (FBG) ≤8.8 mmol/l). 15 The strategies for improving blood perfusion included keeping warm, smoking cessation, and the combined use of vasodilator and antiplatelet aggregation drugs (aspirin, dipyridamole, prostaglandin, or clopidogrel). The offloading therapies were as follows: During hospitalization, all the patients were asked to elevate their affected leg with a cushion.…”
mentioning
confidence: 99%